TRAF-STOP alleviates osteoclastogenesis in periodontitis - Huang, Yaxian; Wu, Jinyan; Zhan, Chi; Liu, Rong; Zhou, Zhaocai; Huang, Xin; Tian, Yaguang; Lin, Zhengmei; Song, Zhi (Frontiers in Pharmacology, 2023)
The enhanced osteoclastogenesis contributes to alveolar bone resorption in periodontitis, which increases the risk of tooth loss. To reduce bone destruction, the inhibition of osteoclast development is proposed as a feasible treatment. CD40L-CD40-TRAF6 signal transduction plays a crucial role in inflammation, but how it regulates osteoclast activity in periodontitis has not been elucidated. In this study, we showed the potential role of CD40L-CD40-TRAF6 signaling in periodontitis. CD40L obviously promoted osteoclast formation and bone resorption capacity in vitro. Mechanistically, we found that osteoclastogenesis was enhanced by the overexpression of NFATC1 and NF-κB activation. Importantly, osteoclast activity was effectively suppressed by TRAF-STOP, a small molecular inhibitor of TRAF6. Furthermore, local injection of TRAF-STOP-loaded injectable PLGA-PEG-PLGA hydrogel could alleviate ligation-induced periodontitis in vivo. Taken together, TRAF-STOP shows promising clinical efficacy in periodontitis through alleviating osteoclastogenesis.